Prenatal diagnosis and postnatal outcomes of absent pulmonary valve syndrome: A case series with genetic and hemodynamic insights - Arslanoğlu, Tuğçe; Alpay, Verda; Özyılmaz, İsa (The European Research Journal, 2025)
Objectives: This study therefore aims to determine the perinatal prognosis and delineate the key risk factors associated with outcomes in fetuses with a prenatal diagnosis of absence of pulmonary valve syndrome (APVS), with particular emphasis on Doppler ultrasound parameters, the presence of extracardiac anomalies, and comprehensive genetic findings - including rare monogenic mutations - as significant contributors to the observed perinatal course. Methods: This retrospective study included eight fetuses diagnosed with absent pulmonary valve syndrome (APVS) between 2020 and 2024 at a tertiary perinatology referral center. One patient with major extracardiac anomalies was electively terminated and excluded from the outcome analysis. For the remaining seven fetuses, detailed fetal echocardiographic assessments—including cardiac anatomy and Doppler hemodynamic parameters - were evaluated alongside genetic testing results (prenatal and/or postnatal), associated extracardiac anomalies, and postnatal clinical and surgical outcomes. Results: Among eight fetuses prenatally diagnosed with APVS, one case was electively terminated due to major extracardiac anomalies and excluded from further analysis. All of the remaining seven cases resulted in live births. Four neonates underwent surgical intervention, three of whom survived postoperatively, yielding a surgical survival rate of 75%. Two fetuses that developed hydrops fetalis died in the early postnatal period before surgery could be performed. The overall perinatal mortality rate was 57.1%. Clinically significant genetic anomalies, including trisomy 21, 22q11.2 deletion, and a novel ABAT gene mutation detected via prenatal whole-exome sequencing, were identified in three patients (42.9%). Nonsurvivors were more likely to present with an absent ductus arteriosus and severely dilated pulmonary arteries. Conclusions: Our study highlights that prognosis is more strongly influenced by prenatal hemodynamic markers - such as pulmonary artery velocities, ductus arteriosus status, and hydrops - than by anatomic subtype. The identification of both common chromosomal anomalies and novel ABAT gene mutations underscores the value of comprehensive genetic evaluation.